Pembelajaran Tari embelajaran Tari Melalui Program Nyantrik Untuk Meningkatkan Keterampilan Tari Di Sanggar Tari Laras Aji Tulungagung - Husna Azizah; Retnayu Prasetyanti Sekti (Universitas Negeri Surabaya, 2026)
Dance learning is a process of developing the ability of an artistic form that uses rhythmic body movements to express beauty. The reason for interest in the topic of writing lies in the nyantrik program in dance training at the Laras Aji Dance Studio. This study aims to describe the implementation of dance learning and the results of learning dance skills through the nyantrik program analyzing the implementation of dance learning through the nyantrik program at the Laras Aji Dance Studio in Tulungagung. The research method used a qualitative approach. The results of the study show that dance learning occurs through the student learning process by observing, imitating and being guided in a real context. The conclusion of this study is that the implementation of the dance learning process through the nyantrik program at the Laras Aji Dance Studio has the main objective of forming students who are able to master dance material thoroughly, both from the aspects of memorization of movements, quality of form, accuracy of technique, and appreciation. The results of learning dance skills directly provide changes in the dancing abilities of nyantrik students at the Laras Aji Dance Studio to improve dance skills and a deeper understanding of traditional dance art.